2009
DOI: 10.1002/cne.22073
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral projections from rat MI whisker cortex to the neostriatum, thalamus, and claustrum: Forebrain circuits for modulating whisking behavior

Abstract: In rats, whisking behavior is characterized by high-frequency synchronous movements and other stereotyped patterns of bilateral coordination that are rarely seen in the bilateral movements of the limbs. This suggests that the motor systems controlling whisker and limb movements must have qualitative or quantitative differences in their interhemispheric connections. To test this hypothesis, anterograde tracing methods were used to characterize the bilateral distribution of projections from the whisker and forep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
68
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 73 publications
(126 reference statements)
18
68
1
Order By: Relevance
“…4, this shift in CS labeling with respect to the Rf was confirmed in coronal sections from a case in which FG was injected into the MI whisker region. Consistent with other findings in our lab (Alloway et al 2009), we observed a continuous and gradual decline in the density of CS labeling at more caudal sections. Our tangential reconstructions also confirm previous reports indicating that CS labeling is greater in the ipsilateral than in the contralateral hemisphere (Li et al 1986;Sloniewski et al 1986;Sadowski et al 1997).…”
Section: Claustrumsupporting
confidence: 94%
See 1 more Smart Citation
“…4, this shift in CS labeling with respect to the Rf was confirmed in coronal sections from a case in which FG was injected into the MI whisker region. Consistent with other findings in our lab (Alloway et al 2009), we observed a continuous and gradual decline in the density of CS labeling at more caudal sections. Our tangential reconstructions also confirm previous reports indicating that CS labeling is greater in the ipsilateral than in the contralateral hemisphere (Li et al 1986;Sloniewski et al 1986;Sadowski et al 1997).…”
Section: Claustrumsupporting
confidence: 94%
“…Furthermore, differences in the amount of bilateral coordination of these body parts should be matched by corresponding differences in the interhemispheric connections of the whisker and forelimb regions in MI. In support of this view, we recently found that the MI whisker region projects more extensively to both sides of the thalamus, neostriatum, and other subcortical brain regions when compared to projections from the MI forepaw region (Alloway et al , 2009.…”
Section: Introductionmentioning
confidence: 88%
“…Notably, studies with unilateral intranigral 6-hydroxydopamine (6-OHDA) application to model Parkinson's disease (PD) found similar findings of increased D 2 receptor densities in the contralateral caudate-putamen [49,50]. There is also histologic evidence for interhemispheric projections from the striatum to the motor cortex [51], and upon lesioning, evidence of increased sprouting from intact to damaged hemispheres [52]. From our observations, it also appears as if reactive compensation is not limited to striatal structures only.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have examined the architecture and connectivity of motor cortex in rats and mice [Donoghue and Parham, 1983;Porter and White, 1983;Cicirata et al, 1986;Alloway et al, 2009;Colechio and Alloway, 2009] (see above for studies of cortical architecture). In some studies, cortex immediately rostral to S1 is reported to contain a small transitional zone with a reduced layer 4 compared to S1 and moderate myelination [Chapin and Lin, 1984;Campi and Krubitzer, 2010;Cooke et al, 2011].…”
Section: Motor Cortexmentioning
confidence: 99%